The Role of Postgraduate International Students in the Process of Internationalization of Higher Education - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (International Islamic University of Malaysia (IIUM), 2016)
This study was conducted to assess the role of interactions among international students from different nationalities on the process of internationalization of Malaysian higher education. An embedded design of mixed methods with the predominant role of the quantitative method was applied to conduct this study. The participants of this study were 118 international postgraduate students from a Malaysian public university, and based on their personal agreements, six of them were interviewed as well. Based on the results, the presence and persuasions of students from their countries at universities and the emerging reputation of public universities in the host country were the main reasons that encouraged international students to enroll in the university. The findings of this study also illustrated that almost all participants of this study shared some information about the quality and standards of higher education in the host country with their friends in their own countries, and encouraged some students to join the mentioned university and other universities in the country. Generally, the findings of this study confirmed the positive role of foreign students in assisting the increase in the number of international students, and also on the process of internationalization of higher education. The findings of this study may help universities to reap more benefits from their international students, and also may encourage students to have better academic achievements through their interactions with their peers from different nationalities.